A Multilevel Study of Change-Oriented Leadership and Commitment: The Moderating Effect of Group Emotional Contagion - Lee MH; Wang C; Yu MC (Psychology Research and Behavior Management, 2023)
Meng-Hsiu Lee,1 Chan Wang,2 Ming-Chu Yu3 1Department of Management Sciences, Tamkang University, New Taipei City, Taiwan; 2School of Humanities, Jinan University, Zhuhai City, People’s Republic of China; 3Department of Public Administration and Management, National University of Tainan, Tainan City, TaiwanCorrespondence: Chan Wang, School of Humanities, Jinan University, 206 Qianshan Road, Zhuhai City, Guang Dong Province, 519070, People’s Republic of China, Tel +86 0756 8505920, Email mschanw@163.comPurpose: The purpose of this study is to explore the effects of change-oriented leadership on employee change commitment, and the underlying cross-level mediating and moderating effects.Design and Methodology: Multilevel analysis of data from 583 respondents in 55 major manufacturing firms in China from 2021, reveals that change-oriented leadership explains the significant variance in change commitment. Based on Emotions as Social Information Theory and Social Exchange Theory, this study investigates the relationship between change-oriented leadership and change commitment fully mediated by emotion regulation.Findings: This study also confirms that positive group emotional contagion has moderating effects on the relationship between change-oriented leadership and emotion regulation. In addition, negative group emotional contagion has moderating effects on the relationship between emotion regulation and change commitment. Furthermore, the moderated mediation of negative group emotional contagion is identified.Originality and Value: This study makes a unique contribution through its multilevel approach to examining the relationship between leadership, emotion, and commitment during organizational change.Keywords: change-oriented leadership, change commitment, group emotional contagion, emotion regulation, multilevel moderated mediation